Complete mitochondrial genome and the phylogenetic position of the brown-spotted grouper Epinephelus chlorostigma (Perciformes: Epinephelidae). (1st November 2016) - Chen, Xiao; Chen, Hao; Yang, Weidi; Lin, Lingling; Liu, Min
Abstract: The complete mitogenome of the brown-spotted grouper Epinephelus chlorostigma was determined in this study. It is 16, 894 bp in length, containing 37 genes with the typical order and transcriptional direction in the vertebrates. The overall nucleotide composition is: 28.7% A; 28.0% C; 16.3% G and 27.0% T. The lengths of 22 transfer RNA (tRNA) genes range from 67 (tRNA- Cys ) to 76 (tRNA- Leu1 ) bp. Two start codons (GTG and ATG) and two stop codons (TAG and TAA/T) were found in the protein-coding genes. The nodes of phylogenetic tree were strongly supported based on the complete mitogenomes of available groupers. The phylogenetic results suggested E. chlorostigma is the closest to E. areolatus within the genus Epinephelus.